Unveiling the Welfare Puzzle: Exploring Fertilizer Subsidy Effects on Farmer's Earnings in Indonesia - Putri, Mega Amelia; Karimi, Syafruddin; Ridwan, Endrizal; Muharja, Fajri (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
This study investigates the unresolved issue of how fertilizer subsidies affect paddy production and farmer income, a critical aspect of Indonesia's agricultural policy that has not been fully understood. By analyzing panel data from 33 provinces between 2019 and 2022 using the Generalized Least Squares (GLS) method, the research explores both income dynamics and productivity. Results reveal that NPK and SP36 fertilizers boost paddy yields by 0.198% and 0.155%, respectively, while UREA and ZA have no significant impact on production. Additionally, rising wages reduce production by 1.343% but increase farmer income by 0.332%. These findings highlight the complexity of balancing productivity with farmer welfare, suggesting that while fertilizer subsidies can enhance yields, they are not a universal solution. Policymakers must consider multifaceted approaches that address both productivity and sustainable income growth to ensure long-term welfare improvements for Indonesian farmers.